2000
DOI: 10.4049/jimmunol.165.6.2975
|View full text |Cite
|
Sign up to set email alerts
|

EBV Persistence Involves Strict Selection of Latently Infected B Cells

Abstract: EBV is found preferentially in IgD− B cells in the peripheral blood. This has led to the proposal that the recirculating memory B cell pool is the site of long-lived persistent infection. In this paper we have used CD27, a newly identified specific marker for memory B cells, to test this hypothesis. We show that EBV is tightly restricted in its expression. Less than 1 in 1000 of the infected cells in the peripheral blood are naive (IgD+, CD27−) and <1 in 250 are IgD+ memory cells. Furthermore, EBV was u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
74
1
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(84 citation statements)
references
References 38 publications
(48 reference statements)
8
74
1
1
Order By: Relevance
“…Covert infections by iridoviruses have been reported in insects (reviewed in Williams et al, 2005), although it is not clear whether these infections are quiescent as they are in mammals (i.e. EpsteinBarr virus [EBV]; Joseph et al, 2000). Quiescence provides a mechanism for viral persistence between episodes of active viral replication.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Covert infections by iridoviruses have been reported in insects (reviewed in Williams et al, 2005), although it is not clear whether these infections are quiescent as they are in mammals (i.e. EpsteinBarr virus [EBV]; Joseph et al, 2000). Quiescence provides a mechanism for viral persistence between episodes of active viral replication.…”
Section: Discussionmentioning
confidence: 99%
“…For example, EBV infects nondividing primary B lymphocytes, and then it triggers cell proliferation. Latently infected B cells express only about 10% of the EBV genome, and they rarely support the lytic form of EBV (Joseph et al, 2000). Furthermore, as a response to a stressor, the virus can be reactivated and become infectious.…”
Section: Discussionmentioning
confidence: 99%
“…This likelihood is supported by several reports indicating that EBV lytic replication occurs in terminal differentiated cells. It is now generally believed that EBV persists in resting memory B cells in which only a small fraction of the infected cells are dividing in the peripheral blood (2,24,27). Moreover, using limiting-dilution reverse transcription-PCR to detect BZLF1 and the early gene BHRF1 demonstrated that about 10 to 20% of the EBV-infected plasma cells are undergoing lytic replication, compared to fewer than 0.1% of EBV-infected germinal center B cells and memory B cells (24).…”
Section: Discussionmentioning
confidence: 99%
“…IgD + CD27 + cells have been characterized as non-switched memory cells or marginal zone-like B cells (9,10). Healthy asymptomatic EBV carriers have low numbers of circulating EBV + B cells that are confined mainly to the IgD 2 CD27 + compartment but can also be found among IgD + CD27 + cells (11,12).…”
Section: E Pstein-barr Virus Infection Is Commonly Contracted Inmentioning
confidence: 99%